Efektivitas Penggunaan Biofilter dengan Proses Anaerob, Aerob, Eceng gondok (Eichhornia crassipes) untuk Menurunkan Kadar TSS, TDS pada Limbah Cair Laundry - Eko Febrianda; Sampe Harahap; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Thelaundryliquid wasteis rich in TSS and TDS and thus need to be processed before being flown to environment. A study aims to reduce the TSS and TDS in that waste has been conducted in January – March 2018. The waste (135 L) was treated using a batch system that was consisted of 2 anaerob and 2 aerob tanks and a Eichhornia crassipes phytoremediation pond. The liquid waste was kept for 10 days in anaerob tanks, 7 days in aerob tanks and 15 days in phytoremediation pond.By the end of the experiment, the TSS reduced from 188 mg/l to 11 mg/l (the effectiveness wasof 94.14%). While the TDS reduced from 1,740 mg/l – 310 mg/l (the effectiveness was 82.18%).Other water quality parameters such as pH was normal and DO was improved. The treated waste was used for rearing Clarias gariepinus (3-4 cm TL) and was kept for 15 days. The survival rate of the fish was 100%. Based on data obtained, it can be concluded that the combination of bio filtersand phytoremediation system using E. crassipes is effective to reduce the TSS and TDS content in the laundry liquid waste. Keyword : waste water, detergent contaminated waste, batch system, waste management